The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/14651858.cd012996.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for reducing sedentary behaviour in people with stroke

Abstract: This is a protocol for a Cochrane Review (Intervention). The objectives are as follows:To determine whether interventions primarily intended to reduce time spent in sedentary behaviour after stroke reduce sedentary time, and whether they modify cardiovascular risk, and reduce the risk of death or secondary vascular events. We will also include interventions intended to reduce the length of prolonged uninterrupted periods of sedentary behaviour (i.e. interventions to fragment or interrupt).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 168 publications
0
29
0
Order By: Relevance
“…In total, the studies included over 22350 participants (two reviews did not report number of participants 24,25 ). Ten reviews were high quality, [26][27][28][29][30][31][32][33][34][35] two moderate, 36,37 three low [38][39][40] and five critically low 24,25,[41][42][43] (supplemental table 2). Nine included a meta-analysis, 25,28,31,32,35,38,41,42,44 of these four were high quality, 28,31,32,35 one moderate quality, 44 one low quality 38 and three critically low quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, the studies included over 22350 participants (two reviews did not report number of participants 24,25 ). Ten reviews were high quality, [26][27][28][29][30][31][32][33][34][35] two moderate, 36,37 three low [38][39][40] and five critically low 24,25,[41][42][43] (supplemental table 2). Nine included a meta-analysis, 25,28,31,32,35,38,41,42,44 of these four were high quality, 28,31,32,35 one moderate quality, 44 one low quality 38 and three critically low quality.…”
Section: Resultsmentioning
confidence: 99%
“…Ten reviews were high quality, [26][27][28][29][30][31][32][33][34][35] two moderate, 36,37 three low [38][39][40] and five critically low 24,25,[41][42][43] (supplemental table 2). Nine included a meta-analysis, 25,28,31,32,35,38,41,42,44 of these four were high quality, 28,31,32,35 one moderate quality, 44 one low quality 38 and three critically low quality. 25,41,42 Fifteen reviews included randomised trials only; the remaining five included a mixture of study designs of interventional studies.…”
Section: Resultsmentioning
confidence: 99%
“…5 A Cochrane systematic review presented trials to reduce sedentary behavior after stroke, with the majority of interventions monitoring physical activity with an accelerometer as an outcome measure. 6 Of importance, a recent study with minor stroke demonstrated that technology alone may be insufficient for changing behavior. 7 In this randomized controlled trial, 2 groups of stroke patients were provided with an accelerometer to self-monitor step-counts during hospitalization and for 3 months after.…”
Section: Physical Activitymentioning
confidence: 99%
“…The primary objectives of this review 1 were to determine whether interventions designed to reduce sedentary behavior after stroke, or interventions with the potential to do so, can reduce the risk of death or secondary vascular events, modify cardiovascular risk, and reduce sedentary behavior.…”
Section: Objectivesmentioning
confidence: 99%